Comparison study: The effect of unmodified and modified graphene nano‐platelets (GNP) on the mechanical, thermal, and electrical performance of different types of GNP‐filled materials. (7th May 2021) - Ka Wei, Kam; Leng, Teh Pei; Keat, Yeoh Cheow; Osman, Hakimah; Sullivan, Martin; Hong, Voon Chun; Ying, Lim Bee; Rasidi, Mohamad Syahmie Mohamad
Abstract: Graphene nano‐platelet (GNP) nano‐fillers were successfully covalently functionalized with carboxylic and epoxide groups as proven by Fourier‐transform infrared spectroscopy. This paper reports the effect of unmodified and modified GNP nano‐fillers on the mechanical, thermal, and electrical performance of GNP‐filled materials. The results show that the mechanical properties of GNP‐filled materials were enhanced with a modified GNP nano‐filler. Among the GNP‐filled materials, the modified epoxy/NR/GNP compatibilized material shows higher flexural and toughness properties. The modified GNP nano‐filler has reduced the thermal stability of the modified compatibilized material. This is because the oxygen‐containing groups (C–O–C and –COOH) on the surfaces of modified GNP nano‐fillers have lower thermal stability; which accelerates the thermal decomposition of the modified material. Modified compatibilized material shows higher electrical conductivity than the unmodified compatibilized material. X‐ray diffraction results proved that d‐spacing of modified GNP nano‐fillers in modified compatibilized material was shortest when compared to unmodified GNP nano‐fillers in unmodified compatibilized material, thus, allowing more electrons to travel at a faster rate through the conductive pathways.